The Effect of Smoking on Eosinophilic Rhinosinusitis with Nasal Polyp in Mouse Model. (2nd September 2014) - Lee, Ki; Mo, Ji‐Hun
Abstract : Objectives: Chronic rhinosinusitis with nasal polyp is a clinically common disease, and cigarette smoking is a major risk factor for airway inflammation. However, little is known about the effects of smoking on eosinophilic rhinosinusitis (ERS) with nasal polyp. A histopathologic and molecular study was performed to investigate the effects of smoking using mouse model of ERS with nasal polyp. Methods: Mice were divided into 4 groups: control group, smoking group, ERS group, and ERS + smoking group (N = 8, each). Histopathologic changes were investigated using several special stainings: Hemotoxylin and eosin for overall inflammation and polyp‐like lesions, Sirius red for eosinophils, Toluidine blue for mast cells, Alcian blue for secretory goblet cells, and Masson's trichrome for collagen fiber. Serum IgE levels and systemic cytokines were determined using enzyme‐linked immunosorbent assay. The expression of vascular endothelial growth factor (VEGF) and HIF‐1a were evaluated by immunohistochemical staining. Results: Smoking enhanced the degree of polyp‐like lesions, eosinophil infiltrations, goblet cell deposition, and subepithelial fibrosis in ERS model. Total and OVA‐specific IgE levels were increased in both ERS groups, however, smoking had no additive effect on them. The systemic cytokines (IL‐4, IL‐6, IL‐17, and IFN‐γ) were also elevated significantly by smoking. Smoking enhanced VEGF expression in nasal epithelial cells, suggesting underlying mechanism of increased polyp formation. Conclusions: Smoking exposure had additive effects on experimental ERS. It resulted from increased local and systemic inflammation, and airway remodeling. Increased VEGF might be its underlying mechanism.